ADDITIVE METALLIZATION OF INJECTION MOLDED CERAMIC COMPONENTS BY A PLASMA-COATING PROCESS - Braun, Thomas; Greiner, Sandra; Diepgen, Antonia; Schröppel, Kerry; Drummer, Dietmar; Franke, Jörg (Proceedings of the SMTA Pan Pacific Microelectronics Symposium, 2017, 2017)
Electronic components are increasingly used in high-temperature environments like automotive and aerospace applications. For these applications, miniaturization is gaining importance so that traditional methods and materials encounter their limits.  Therefore, with high thermal and chemical stability, ceramic materials offer an abundance of possible applications in the electronic circuit board sector. Furthermore, regarding miniaturization and increase of the functional density, electronic and mechanical components have to be merged. Reducing process time an alternative technology has to be found for applying a conductor track on a three-dimensional surface in little time. This paper shows the whole production chain of the manufacturing of a three-dimensional mechatronic integrated device based on ceramics, beginning with the injection molding of different ceramic-based materials in four process steps: compounding, injection molding, two-step debinding and sintering. For metallization of the ceramics, the paper presents an innovative plasma-coating technology. Thereby, a conductor track can be produced in only one process step within a few seconds without pre and post processing and without chemical substances. The system consists of two units: In one, the plasma generation module and the metal powder storage are hosted. In the other, the handling system and the plasma nozzle are located. In the plasma nozzle, the stream of carrier gas is ionized by an electric arc and is turned into a plasma state. The nozzle is fed with copper powder by two independent inert gas flows. Due to the high energetic plasma flame, the metal powder is melted and accelerated toward the surface of the substrate. A six-axis robot is used for handling the specimen and regulates the process speed, the distance between the nozzle and ceramic basic substrate as well as the applied layers to obtain the desired electrical and mechanical properties. The paper also shows the influence of the most important parameters for the metallization process, which can be summarized in four main groups: the used substrate, the metal powder, the plasma generation and the handling. After that, different passivation materials are tested to protect the generated copper conductor tracks from corrosion and mechanical influences. Furthermore, the paper will describe the effects of using conductive adhesive and soldering paste for contacting electrical components on the plasma-coated surface. The paper also presents investigations regarding the electrical resistance of the conductor tracks, the adhesive strength of the additively applied metal structures, and the maximum resistance to mechanical load before removing the electronic parts. The results of long-term tests deliver valuable information about the capabilities for a permanent use in automotive applications. Due to the basic research, the paper will present different demonstrators, which will show various areas of applications. To show the advantages of ceramic materials, three-dimensional circuit carriers are exposed to extreme conditions like heat and chemicals. Due to the high temperature resistance, this technique can be used to build a temperature sensor, which can be installed near to hot engines or inside a battery for directly measurement of the temperature.
Keywords: MID; Plasma-Coating; Plasmabeschichten; Additive Metallisierung